Introduction to science of Quran - Ahmad, Nadzrah (2017)
This book will discuss comprehensively the basic issues and principles which lead to the true understanding of the Qur’an. The main issues to be focused on in this book include historical background of sciences of the Qur’an, the revelation of the Qur’an (wahy), the history behind the compilation of the Qur’an, the classification of the surah into Makki and Madani, the background of revelation (asbab an-nuzul), the discussion on ayat muhkamat and ayat mutashabihat, the abrogation (naskh) in the Qur’an, the inimitability aspect of the Qur’an, the commentary of the Qur’an and the schools of tafsir in different ages, and the co-relationship between the ayat in the Quran.